The Impact of Antenna Characteristics on Target Signal Detection in FMCW-Radar System Simulations for Automotive Applications - Dudek, Manuel; Nasr, Ismail; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (IEEE Radio Wireless Symposium (RWS), 2012)
In this scientific paper a versatile system simulation environment is introduced that enables investigations on millimeter-wave FMCW-radar sensors. With respect to the latest developments in automotive radar the simulator combines an RF-frontend simulation engine and a 3D ray-tracing tool to take the effects of the radar channel into account. Furthermore different antenna characteristics can be generated by the phased-array radar topology implemented to examine not only the behavior of the RF-frontend but the impact of the concrete traffic situation on the whole sensor system. Therefore development engineers are actively assisted with their task to design new accurate and reliable systems, thus enabling the transition from current pure comfort systems to future systems including an increased number of safety functions. To demon-strate the usability of this advanced simulation approach for the development of future radar sensors a typical traffic scenario is calculated showing not only the impact of the antennas’ beamwidth and side-lobes on target signal detection, but also the performance of the simulation environment built-up.
elib2cris::1512001600,dudek2012